Prehospital care for ovarian cancer in Catalonia: could we do better in primary care? Retrospective cohort study - Mercè Marzo-Castillejo; Josep M Borras; Carmen Vela-Vallespín; Paula Manchon‐Walsh; Luisa Aliste (BMJ Open)
Objective To assess the impact of prehospital factors (diagnostic pathways, first presentation to healthcare services, intervals, participation in primary care) on 1-year and 5-year survival in people with epithelial ovarian cancer (EOC).Design Retrospective quasi-population-based cohort study.Setting Catalan Integrated Public Healthcare System.Participants People with EOC who underwent surgery with a curative intent in public Catalan hospitals between 1 January 2013 and 31 December 2014.Outcome measures Data from primary and secondary care clinical histories and care processes in the 18 months leading up to confirmation (signs and symptoms at presentation, diagnosis pathways, referrals, diagnosis interval) of the EOC diagnosis (stage, histology type, treatment). Diagnostic process intervals were based on the Aarhus statement. 1-year and 5-year survival analysis was undertaken.Results Of the 513 patients included in the cohort, 67.2% initially consulted their family physician, while 36.4% were diagnosed through emergency services. In the Cox models, survival was influenced by advanced stage at 1 year (HR 3.84, 95% CI 1.23 to 12.02) and 5 years (HR 5.36, 95% CI 3.07 to 9.36), as was the type of treatment received, although this association was attenuated over follow-up. Age became significant at 5 years of follow-up. After adjusting for age, adjusted morbidity groups, stage at diagnosis and treatment, 5-year survival was better in patients presenting with gynaecological bleeding (HR 0.35, 95% CI 0.16 to 0.79). Survival was not associated with a starting point involving primary care (HR 1.39, 95% CI 0.93 to 2.09), diagnostic pathways involving referral to elective gynaecological care from non-general practitioners (HR 0.80, 95% CI 0.51 to 1.26), or self-presentation to emergency services (HR 0.82, 95% CI 0.52 to 1.31).Conclusions Survival in EOC is not associated with diagnostic pathways or prehospital healthcare, but it is influenced by stage at diagnosis, administration of primary cytoreduction plus chemotherapy and patient age.